Al-Shaikh Ghulam Al-Murtaza and his contribution to Arabic Literature (Analytical Study) : الشيخ غلام المرتضی واسهامه في الأدب العربي - -Zaman, Dr. Fakhar-ul; Naheed , Dr. Najma (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Al-Shaikh Ghulam Al-Murtaza's knowledge of Arabic literature is a piece of evidence of the subcontinent's rich diverse literary tradition. His ability to write fluently in Arabic alongside Persian and Urdu demonstrates his depth of knowledge and linguistic versatility. His contributions to Arabic literature contain valuable insight into religious and theological issues. In this article, an in-depth analysis of Al-Shaikh Ghulam Al-Murtaza's literary work sheds light on the themes and styles he adopted in his Arabic works. It examines the impact of his diverse background on his writing and the impact his work had on the literary world of the time. His writings on various subjects in the Islamic discipline are a vital source of information for both researchers to have a deeper understanding of the religion and its historical development. The article also considers how Al-Shaikh Al-Ghulam Murtaza's Arabic writings are received among native Arabic scholars. The recognition and admiration he has received from the Arab community is a testament to his fluency in the Arabic language and his ability to appeal to a wider audience across the subcontinent.